Admission Systemic Immune-Inflammation Index and Its Association with High Thrombus Burden and No-Reflow in ST-Segment Elevation Myocardial Infarction: A Retrospective Cohort Study - Wayan Ardyana Prastara; Hendy Wirawan; I Kadek Susila Surya Darma; I Made Junior Rina Artha; I Made Putra Swi Antara; I Wayan Gede Artawan Eka Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: ST-segment elevation myocardial infarction (STEMI) is a thrombo-inflammatory emergency, and successful epicardial recanalisation during primary percutaneous coronary intervention (PCI) does not always restore myocardial perfusion. The Systemic Immune-Inflammation Index (SII), derived from routine platelet, neutrophil and lymphocyte counts, may reflect thrombo-inflammatory risk. This study evaluated the association of admission SII with high thrombus burden and no-reflow in STEMI patients undergoing primary PCI. Methods: This STROBE-compliant retrospective cohort study consecutively sampled 118 STEMI patients at Prof. dr. I.G.N.G. Ngoerah General Hospital, Denpasar. High thrombus burden was defined as TIMI thrombus grade 4-5 and no-reflow as post-procedural TIMI flow grade =2. The optimal SII cut-off was derived by receiver operating characteristic analysis (Youden index); associations were assessed with chi-square/Fisher tests and modified Poisson regression with robust standard errors. Results: High thrombus burden occurred in 99 patients (83.9%) and no-reflow in 16 (13.6%). High SII was associated with high thrombus burden (90.8% vs 75.5%; relative risk 1.203, 95% CI 1.013-1.428; p=0.025) and no-reflow (20.0% vs 5.7%; relative risk 3.53, 95% CI 1.062-11.753; p=0.024), persisting after adjustment (adjusted relative risk 1.194 and 3.226, respectively). Discrimination was weak-to-modest (AUC 0.597 and 0.674). Conclusion: Admission SII was independently associated with high thrombus burden and no-reflow but had insufficient accuracy for standalone prediction, supporting its role as a simple adjunctive marker rather than a definitive predictor.